Molecular identification and phylogenetic analysis of suaeda maritima from parangipettai coastal areas, southeast coast of india - G, Anbarasi; B, Vishnupriya (Kongunadu Research Journal, 2020)
Conventional taxonomy is limited with delineating species and controversies arise with DNA barcoding based identifications. Hence, an alternative supporting approach is very much needed to identify species and differentiate them within the species based on the genetic material. 18S rRNA genes have been particularly helpful in analyzing phylogeny at the species level. In addition, bioinformatics which represents a new, growing area of science uses computational approaches to answer biological questions. Salt tolerant costal salt marsh plant of Suaeda maritima was selected for 18s rRNA sequencing to solve the ambiguity in its species level identification. Similarity search of study species shared 99% similarity with 5 species of Atriplex canescens clone s128, Atriplex torreyi var. griffithsii clone p508, Spinacia oleracea, Oenothera laciniata clone,Beta vulgaris. Phylogenetic tree infer that S.maritima is closely related to Spinacia oleracea and Oenothera laciniata. Atriplex canescens (fourwing saltbush), Atriplex torreyi and Phaulothamnus spinescens, Celosia argentea found to be closely related and are in one group. Hence, this study result clearly shows thus study species evaluated from angiosperm and provides key step in understanding the evolution of salt tolerance in angiosperm.